Chemical and Hygienic Qualities of Stripped and Burnt Sheep Meat in Southern Benin - SALIFOU, CHAKIRATH FOLAKE ARIKE; AHOUANSE, GLWADYS GLORIA AMEN; KIKI, PASCAL SEGBEGNON; DOTCHE, IGNACE O; AGOSSA, RAOUL; ISSIFOU, MIKIDADOU; YOUSSAO, ISSAKA (My University, 2022)
Background and Objective: Burning and stripping are the main methods of dressing sheep slaughtered in Benin's slaughterhouses. This study aims to compare the quality of sheep meat according to the type of dressing in Southern Benin. Materials and Methods: The hygienic quality was assessed through research on total vial counts (TVC), enterobacteria, E. coli , Staphylococcus aureus and Salmonella in 70 samples (35 from each dressing method). Chemical analyses were carried out on 40 samples of Longissimus dorsi (20 from each dressing method). Results: TVC, Enterobacteriaceae and E. coli count of burnt sheep carcasses (5.10±1.37, 4.12±0.59 and 2.06±0.91 log CFU cmG2, respectively) were significantly higher (p<0.05) than those of stripped sheep carcasses. Salmonella was only detected in 7 samples of burnt sheep meat. Meat chemical composition did not change except for the protein content which is higher in burnt sheep. Conclusion: This study shows that the hygienic quality of meat from sheep slaughtered in the south Benin slaughterhouse remains inadequate, regardless of the dressing method.
Keywords: quality; burnt; stripped; meat; Sheep; microorganisms; E. coli; organoleptic